Traditional Uses, Phytochemical Constituents and Pharmacological Properties of Averrhoa carambola L.: A Review - Luan, Fei; Peng, Lixia; Lei, Ziqin; Jia, Xiyu; Zou, Junbo; Yang, Yan; He, Xirui; Zeng, Nan (Frontiers in Pharmacology, 2021)
Averrhoa carambola L. (star fruit) is an edible fruit that is extensively cultivated in southern China, Southeast Asia, India, and northern South America. It has a sweet and juicy taste and is frequently used in fruit salads and fruit platters, as a garnish in cocktail drinks and beverages, or squeezed into juice and served as a beverage. Traditionally, it has been used for treating diabetes and diabetic nephropathy, arthralgia, vomiting, lithangiuria, coughing, hangovers, and chronic paroxysmal headache for thousands of years. Currently, approximately 132 compounds have been isolated from A. carambola. Among them, flavonoids, benzoquinone, and their glycosides have been considered as biologically active substances, which are responsible for various biological activities. Pharmacological studies have revealed that crude extracts or monomeric compounds from A. carambola exhibit multiple bioactivities, such as anti-oxidant, anti-hyperglycemic, anti-obesity, anti-hyperlipidemic, anti-tumor, anti-inflammatory, hepatoprotective, cardioprotective, anti-hypertensive, neuroprotective, and others. Thus, A. carambola is a valuable treatment in Chinese medicine with therapeutic potential for multiple diseases, especially diabetes and diabetes-related diseases. Even though it is a very promising candidate in the development of functional food and the pharmaceutical industry, reports on its bioactivities have only been conducted in vivo and in vitro and there is a gap in research regarding clinical settings and safety. This review therefore provides a comprehensive and systematic overview of current progress on botany, ethnopharmacology, phytochemistry, pharmacology, and toxicity of A. carambola, providing a valuable reference for further developments and applications of A. carambola in the pharmaceutical industry and functional food.